Board Characteristics, Type of Insurance and Performance In Indonesia Sharia Insurance Companies - Hikmah Endraswati; Bayu Tri Cahya (IQTISHADIA, 2020)
The purpose of this study was to examine the influence of the board characteristics on the performance of Indonesia sharia insurance companies with insurance types as moderating variable. The board characteristics in this study are the size of board directors, the size of board commissioners, the proportion of women in board directors, and the proportion of women in board commissioners. This study uses 22 sharia insurance business units as a sample with the periode of 2014-2019. We use purposive sampling as a sampling technique. Multiple regression with split sample is used in this research as technical analysis. The results showed that the size of the board directors influence performance negatively. In addition, the type of insurance moderate the influence size of board directors and the proportion of women as directors on performance. There are differences for size of the board of commissioners and the proportion of women as board commissioners.